EMERGING TECHNOLOGIES APPLIED TO THE POULTRY PRODUCTION CHAIN AS “PRECISION TOOLS” - Mollo Neto, Mario (Seven Editora, 2025)
According to the 2024 Annual Report from the Brazilian Animal Protein Association (ABPA), Brazil produced 52.4 billion eggs in 2023, with 99% allocated to the domestic market and 1% exported. This production scale demands that poultry operations integrate advanced data-driven methodologies to optimize performance and meet evolving consumer expectations. As a global benchmark, the Brazilian poultry sector must adopt innovative technologies tailored to local conditions, ensuring product quality and maintaining competitive advantage. Strategic management now requires real-time decision-making supported by digital platforms and Industry 4.0 technologies, with emphasis on animal welfare, environmental sustainability, and corporate social responsibility. The rapid evolution of Internet of Things (IoT) systems and cloud-based infrastructures underpins the emergence of smart agriculture. These technologies enable the deployment of sophisticated mathematical models and real-time algorithms for predictive analytics and operational optimization. Research findings highlight the applicability of emerging precision technologies across the poultry production chain. These tools enhance analytical capabilities and support managerial decision-making, surpassing earlier frameworks such as Smart Poultry Farming. By streamlining processes, reducing operational costs, and generating new business opportunities, digital transformation reinforces sectoral competitiveness and aligns with strategic, environmental, and social governance objectives. DOI: https://doi.org/10.56238/sevened2025.036-153